Efeitos da exposição aguda à frutose em anéis isolados de aorta de ratos - Pereira, Camila Almenara Cruz (2017)
It has been already described that fructose can acutely interferes on cardiovascular function in humans and in animals, but the mechanisms underlying this effect remain unclear. Thus, we sought to test whether fructose can affect the vascular function without the interference of its metabolic effect. We exposed aortic segments from Wistar rats to 4, 20 or 40 mM of fructose or mannitol for 30 minutes and then evaluated the vascular responses to vasoactive agents. We also analyzed oxygen consumption by cultured endothelial cells after fructose supplementation (1 and 10 mM). Fructose increased the response to phenylephrine and reduced endothelium dependent relaxation elicited by acetylcholine, but did not change vascular responses to sodium nitroprusside.